Voting Behaviour in India-An analysis (International Journal of Food and Nutritional Sciences, 2022)
Voting behaviour, also known as electoral behaviour, involves understanding the factors and reasons which influence voting patterns. To interpret voting behaviour both political science and psychology expertise were necessary and therefore the field of political psychology emerged including electoral psychology. This article will shed light on the meaning and the determinant factors of voting behaviour. The Secondary data which has been collected from books, journals and periodicals is used to analyse the various factors in this study.